REKONSTRUKSI VERIFIKASI PARTAI POLITIK SEBAGAI PENEGAKAN ASAS EFISIENSI DAN EFEKTIVITAS PEMILIHAN UMUM - Ahmad Gelora Mahardika (Faculty of Law - Tarumanagara University, 2020)
As a stage in the implementation of elections, verification of political parties is important. Aside from being an effort to create a simple multi-party system, the implementation of verification og political party is also an effort to ensure that the Political Parties are indeed eligible to contest in general elections. However, the verification should be carried out only once as stipulated in the legislation. However, in practice, new political parties must undergo verification twice with similar requirements, namely verification to obtain a legal entity status as stipulated in Law Number 2 of 2011 concerning Political Parties and verification to become an election participant regulated in Law Number 7 of 2017 concerning general elections. This raises the potential for reduplication of verification by the state of new political parties which then has implications for ineffectiveness, inefficiency and violations of the principle of justice. The research method in this article is normative juridical. The conclusion in this study is the implementation of political party verification which is currently happening inefficiently because it led to reduplication so that it needs to be reorganized.